Simulasi Antrian Pembuatan Sim Di Sat Lantas Polres Deli Serdang Menggunakan Metode Eksponensial - Debirahayu; Hasanul Fahmi (Sisfokomtek, 2020)
Queuing simulation is very much needed by Sat. Then the Deli Serdang Police because the number of queues every day is very long making it difficult for Sat Then to serve applicants for a driving license (SIM). Judging from the length of the queue every day, Sat Then the Deli Serdang Police need a system that can make it easier for Sat Lantas to determine the most efficient time in queuing. Because currently the system being used is still very manual, thus making the prospective driver's license (SIM) applicant become bored waiting to be served even though the facilities provided by the Sat Lantas are quite adequate. So to overcome the long queues every day, a queue simulation is needed to solve the problem of the fastest time in queuing using the exponential method.